2004
DOI: 10.2320/matertrans.45.1194
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Phase Separation in an Fe<SUB>70</SUB>Nb<SUB>10</SUB>B<SUB>20</SUB> Glass Studied by Advanced Electron Microscopy Techniques

Abstract: Advanced techniques of electron microscopy were employed for analyzing a local structure of an as-formed Fe 70 Nb 10 B 20 metallic glass. From nano-diffraction with an electron probe size of 1 nm, diffraction patterns of bcc-Fe and Fe-boride were observed which indicated an occurrence of nano scale phase separation in the glass. Atomic pair distribution function (PDF) analysis of the glass was also performed by means of precise electron diffraction intensity analysis taking advantage of energy-filter and imagi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…The salt and pepper contrast typical of amorphous materials was observed in both the images. We cannot see any crystalline regions, except medium range ordered regions which were already reported in the previous paper [9,10]. Therefore, it was confirmed that the specimens were not crystallized yet at these stages.…”
Section: Resultssupporting
confidence: 83%
“…The salt and pepper contrast typical of amorphous materials was observed in both the images. We cannot see any crystalline regions, except medium range ordered regions which were already reported in the previous paper [9,10]. Therefore, it was confirmed that the specimens were not crystallized yet at these stages.…”
Section: Resultssupporting
confidence: 83%
“…5,12) In the amorphous Fe 80 B 20 and Fe 70 Nb 10 B 20 alloys, our group already found nanoscale phase separation with bcc-Fe and compound-like local ordered regions by using nanobeam electron diffraction technique together with HREM. 13,14) We now discuss a difference of the glass forming abilities between the two alloys based on the local atomic arrangements derived from the final structure models. The crystalline phases and their basic structural units already found in the ternary Fe-Nb-B system 15) are represented in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The requirement for the three-component rule has been interpreted to originate from the formation, in the supercooled liquid and glassy structure, of unique distorted trigonal prisms and anti-Archimedean prisms consisting mainly of Fe and B or C. These prisms are connected to each other in edge-and face-shared configuration modes through glue atoms of M (M5Ln, Zr, Nb, Mo and Ga) elements. 175,176 As an example, Fig. 2a shows a schematic illustration of the local atomic configurations in Fe-RE-B (RE5rare-earth metals) and Fe-TM-B (TM5transition metals such as Zr, Nb or Mo) glassy alloys derived from the experimental data using the anomalous XRD, pulsed neutron diffraction, high-resolution TEM and reverse Monte-Carlo computer simulation techniques.…”
Section: Structure Of the Glassy Phasementioning
confidence: 99%
“…The local atomic configuration of the M 23 (B,C) 6 phase includes an anti-Archimedean atomic configuration which is similar to that of the Fe-Nb-B glassy alloys. 175,176 It is because of the similarity between the local atomic configurations of the supercooled liquid and the primary precipitate phase that this is the first phase to form during crystallisation of the BMG alloys. It is thus interpreted that the spontaneous formation of the long-range network-like atomic configurations in the supercooled liquid in multi-component alloy systems with at least three components is the origin for the high stability of the supercooled liquid against crystallisation in Fe-based BMG alloys.…”
Section: Structure Of the Glassy Phasementioning
confidence: 99%